Hubungan Antara Kelekatan Orang Tua dan Harga Diri Terhadap Agresivitas Remaja SMA di Kecamatan Pontang - Lia Amaliah Putri; Karlina Marjo, Happy; Herdi, Herdi (Jurnal Ragam Pengabdian, 2026)
This study aims to examine the relationship between parental attachment, self-esteem, and student aggressiveness using a quantitative correlational approach. The population consisted of 435 eleventh-grade students from five high schools in Pontang, with a sample of 209 participants selected using the Slovin formula at a 5% error rate. Data were collected through three validated and reliable instruments: the Inventory of Parent and Peer Attachment (IPPA) with 25 items to assess parental attachment, the Rosenberg Self-Esteem Scale (RSES) with 10 items to measure self-esteem, and the Buss–Perry Aggression Questionnaire (BPAQ) with 29 items to evaluate aggressive behavior. Data analysis employed multiple correlation techniques to determine the relationships among the variables. The findings revealed a significant negative relationship between parental attachment and student aggressiveness, indicating that stronger emotional bonds with parents are associated with lower levels of aggressive behavior. In addition, parental attachment and self-esteem simultaneously had a significant influence on adolescent aggressiveness. Students with higher self-esteem and better-quality relationships with their parents demonstrated a lower tendency toward aggression. These findings highlight the importance of fostering supportive family relationships and positive self-esteem as protective factors against aggressive behavior. The study also provides practical implications for school guidance and counseling services in designing family-based preventive interventions and psychological support programs to promote students' social and emotional well-being.